Inverses for normal modal operators - Humberstone, L; Williamson, T (Springer, 1997)
Given a 1-ary sentence operator O, we describe L - another 1-ary operator - as a left inverse of O in a given logic if in that logic every formula φ is provably equivalent to LOφ. Similarly R is a right inverse of O if φ is always provably equivalent to ORφ. We investigate the behaviour of left and right inverses for O taken as the □ operator of various normal modal logics, paying particular attention to the conditions under which these logics are conservatively extended by the addition of such inverses, as well as to the question of when, in such extensions, the inverses behave as normal modal operators in their own right.